Arched windows, Darabshaw House - Ghosh, Ayan (2023)
Semi-circular arched windows with moldings and projecting imposts on the ground floor of Darabshaw House which was once open and let in natural light and air. The sealing of the windows is symptomatic of changes made in buildings at Ballard Estate in order to accommodate modern building requirements, like the installation of air conditioning units.